COMPREHENDING NARRATIVE: THE COGNITIVE DIMENSION - Jacobs, Roderick A. (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract Readers of narratives construct complex mental models or ‘spaces’ within which to locate themselves. During this process, readers construct, activate, and adjust a spatio-temporal focus to integrate interpretation of individual sentences in a global interpretation. This focus, the ‘deictic center’, shifts constantly. Although linguistic markings help orient the readers, they must draw not only on complex inferential skill but also schematic socio-cultural knowledge. This can create difficulties for readers from other linguistic and cultural environments. Examples from several narratives and a poem are examined, and the cognitive skills required are considered. In each, a base reality “of this time, of that place’ is established, and readers are moved from that mental space to spaces representing other times and places, real and hypothetical, which may include counterparts of events and participants already encountered. The notion of ‘sameness’ is thus a complex one, since it links counterparts across different kinds of spaces. In our examples, each author uses sometimes subtle linguistic markers pointing to sociocultural schemata assumed familiar to the assumed readership. Readers from other social and cultural contexts must surmount the differences in order to construct a plausible cognitive model of the narrative.